THE PHYSIOLOGICAL AND NUTRITIONAL CONTENT CHANGES OF JELUTUNG (Dyera polyphylla (Miq.) Steenis) SEED THROUGH DRYING AND STORAGE - Yuniarti, Naning; Nurhasybi, Nurhasybi (Association of Indonesian Forestry and Environment Researchers and Technicians, 2018)
Seed deterioration is the process of deteriorated seed in view of viability that has changed its physiological and nutritional content. This paper studies the effect of seed drying and seed storage to the viability and biochemical content of jelutung (Dyera polyphylla (Miq.) Steenis) seeds. Completely Randomized Design was used for different level of seed drying time, i.e. 0, 24, 48, 72, 96 and 120 hours, and Completely Randomized Factorial Design was used for the combination of seed drying treatments of 0, 24, 48, 72, 96 and 120 hours in different rooms for seed storage (ambient room, air conditioned room, refrigerator) with variables of moisture content, germination percentage and nutritional content. Result shows that seed drying and seed storage treatments pursue the change of seed viability and nutritional content of jelutung seed. The period of time in seed drying and seed storage siginificantly influence the moisture content, germination percentage and nutritional composition (lipid, carbohydrate, protein). The longer time of seed drying will effect significantly to the moisture content and germination percentage, increasing the lipid and protein and decreasing carbohydrate. Jelutung seed that was stored in air conditioned room had better viability compared to ambient room and refrigerator.